2018
DOI: 10.1002/anie.201712602
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Mechanochemistry: Direct, Room‐Temperature, Solvent‐Free Conversion of Palladium and Gold Metals into Soluble Salts and Coordination Complexes

Abstract: Noble metals are valued, critical elements whose chemical activation or recycling is challenging, and traditionally requires high temperatures, strong acids or bases, or aggressive complexation agents. By using elementary palladium and gold, demonstrated here is the use of mechanochemistry for noble-metal activation and recycling by mild, clean, solvent-free, and room-temperature chemistry. The process leads to direct, efficient, one-pot conversion of the metals, including spent catalysts, into either simple w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 61 publications
0
53
0
Order By: Relevance
“…[57] The ability of mechanochemistry to avoid using [58] or producing toxic substances was put again in evidence during the oxidation of noble metals like gold and palladium into useful metal salts by ball milling (Scheme 5). [59] The mechanochemical approach enabled the oxidation of metal pellets, metal powder or metal wires into well-defined salts using Oxone® [60] and halide salts, thus preventing the use of hazardous reagents such as aqua regia. Although Oxone® (KHSO 5 -1/2KHSO 4 -1/2 K 2 SO 4 ) is clearly less atom economical and its use generates more waste compared with oxidants such as dioxygen or hydrogen peroxide (H 2 O 2 ), Oxone® is a cheap and easy to handle solid reagent, which generates mostly K 2 SO 4 as the only by-product.…”
Section: Gc 3: Less Hazardous Chemical Synthesismentioning
confidence: 99%
“…[57] The ability of mechanochemistry to avoid using [58] or producing toxic substances was put again in evidence during the oxidation of noble metals like gold and palladium into useful metal salts by ball milling (Scheme 5). [59] The mechanochemical approach enabled the oxidation of metal pellets, metal powder or metal wires into well-defined salts using Oxone® [60] and halide salts, thus preventing the use of hazardous reagents such as aqua regia. Although Oxone® (KHSO 5 -1/2KHSO 4 -1/2 K 2 SO 4 ) is clearly less atom economical and its use generates more waste compared with oxidants such as dioxygen or hydrogen peroxide (H 2 O 2 ), Oxone® is a cheap and easy to handle solid reagent, which generates mostly K 2 SO 4 as the only by-product.…”
Section: Gc 3: Less Hazardous Chemical Synthesismentioning
confidence: 99%
“…In the context of making functional products from the simplest precursors,Doetal. used 1-or 2step oxidative mechanochemistry to convert noble metals into water-soluble salts or catalysts, [108] permitting recycling of spent catalysts without harsh chemistry.M ulti-component transformations can also be conducted with gaseous reactants, as shown by gas-templated assembly of hydrogen-bonded frameworks or synthesis of copper(II) N-heterocyclic carbene complexes directly from copper metal, an imidazolium salt and O 2 gas. [109] TheH amilton group reported that making porphyrins, notorious for solvent waste,can mechanochemically be done mechanochemically in yields comparable to solution.…”
Section: Multi-component and Multi-step Reactionsmentioning
confidence: 99%
“…In the context of making functional products from the simplest precursors, Do et al. used 1‐ or 2‐step oxidative mechanochemistry to convert noble metals into water‐soluble salts or catalysts, permitting recycling of spent catalysts without harsh chemistry. Multi‐component transformations can also be conducted with gaseous reactants, as shown by gas‐templated assembly of hydrogen‐bonded frameworks or synthesis of copper(II) N‐heterocyclic carbene complexes directly from copper metal, an imidazolium salt and O 2 gas …”
Section: Complex Structuresmentioning
confidence: 99%